Improving Students' Critical-Thinking Skills Through Student Facilitator and Explaining Model in Momentum and Impulse Topic - Adam Malik; Vitriani Vitriani; Muhammad Minan Chusni (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2018)
This study aims to determine the implementation of cooperative learning models using type Student Facilitator and Explaining (SFAE) and the improvement of students' critical-thinking skills in momentum and impulses topic. We use pre-experiment design, with the one-group pretest-posttest. The population of this study was class X MIA YAS Bandung with the sample of class X MIA 2 amounted to 30 students selected by random technique. We use the observation sheet as the instrument to observe the implementation of teacher and student activities during the cooperative learning model type SFAE. The essay tests are used to measure the improvement of students' critical-thinking skills. The results of the study showed that the implementation of teacher activities was 81% and student activities by 77% in the good category. Increasing students' critical-thinking skills is the medium category with an average normalized gain value of 0.63. Based on the results of hypothesis testing using the paired sample t-test, it was obtained t-count (34.08) > t-table (2.052) which means that Ho was rejected and Ha was accepted. It was concluded that there was an increase in students' critical-thinking skills after applying the SFAE type cooperative learning model to the material of momentum and impulse. Thus, this learning model of type SFAE can be used to improve students' higher-order thinking skills.